Mengenal Lebih Dekat Konseling Gestalt: Sebuah Studi Literatur - Habsy, Bakhrudin All; Fikri, Choiril Ibadiyah; Qurrotussalwa, Fahmida; Septianingtyas, Dwi Lutviani; Rahmah, Dwi Oktavia Naila (Lembaga Yasin AlSys, 2024)
Gestalt counselling is an approach to psychotherapy and counselling that focuses on the counselee's awareness of current experience and the ability to make better choices. This research uses a qualitative method of literature study that aims to introduce gestalt counselling comprehensively, starting from the historical background, basic concepts, goals, therapeutic process, to the various techniques used. Gestalt counselling was born in the 1940s and developed by Fritz Perls, Laura Perls, and Paula Goodman based on various psychological approaches. The essence of gestalt counselling lies in enhancing the counselee's present self-awareness, sense of personal responsibility, personality integration and self-actualisation. The techniques used and discussed include general techniques, frustrating the counselee, externalising techniques, top dog and under dog. The author hopes that this paper can increase the reader's understanding of the intricacies of gestalt counselling so that it can be applied appropriately in the field.